Hydrophilic porous carbon electrode and method for producing the same

By controlling the water contact angle and surface characteristics in the porous carbon electrode and adopting specific heat treatment and electrolytic treatment processes, the problem of insufficient characteristics of the existing porous carbon electrode batteries is solved, and the battery of the redox flow battery is significantly improved performance.

CN111712955BActive Publication Date: 2025-01-10MITSUBISHI CHEM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN201980012740.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-02-15
Filing Date
2019-02-13
Publication Date
2025-01-10
Estimated Expiration
2039-07-15

AI Technical Summary

Technical Problem

The existing porous carbon electrodes have insufficient battery characteristics in redox flow batteries, and higher performance hydrophilic porous carbon electrodes are needed to improve reactive activity and battery performance.

Method used

The sheet-shaped porous carbon electrode formed by bonding carbon fibers through resin carbides is controlled to have a water contact angle between the two sides and the middle portion in the thickness direction within a range of 0 to 15°, and a 0.1 to 5.0 μm is formed on the surface. In non-through holes, Ag, Ti oxide or Sn oxide exists, and the oxidizing gas heat treatment and electrolytic treatment are used to improve its hydrophilicity and reactivity.

Benefits of technology

The high hydrophilicity and reactivity of the porous carbon electrode are achieved, and the battery characteristics of the redox flow battery are significantly improved, and excellent battery performance is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002627013510000211
    Figure BDA0002627013510000211
  • Figure BDA0002627013510000241
    Figure BDA0002627013510000241
Patent Text Reader

Abstract

The present invention provides a hydrophilic porous carbon electrode, which has excellent hydrophilicity, high reaction activity when used in batteries, and can obtain excellent battery characteristics. The hydrophilic porous carbon electrode is a sheet-shaped porous carbon electrode formed by bonding carbon fibers through resin carbide, and the water contact angle θ on both sides of the surface in the thickness direction is A The water contact angle θ in the middle of the thickness direction is 0 to 15°. B The carbon fiber and the binder fiber are formed into sheets, impregnated with a thermosetting resin, and then carbonized in an inert atmosphere at 400 to 3000°C to obtain a porous carbon electrode. The porous carbon electrode is transported, and an oxidizing gas at 400 to 800°C is flowed in a direction perpendicular to the transport direction of the porous carbon electrode to perform heat treatment, thereby hydrophilizing the porous carbon electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hydrophilic porous carbon electrode and a method for producing the same.

[0002] This application claims priority based on Japanese Patent Application No. 2018-025086 filed on February 15, 2018 and Japanese Patent Application No. 2018-025411 filed on February 15, 2018, and the contents of these are incorporated herein by reference. Background Art

[0003] In the electrodes of lithium-ion batteries, fuel cells, redox flow batteries, etc., porous substrates in which short-fiber carbon fibers are dispersed and bonded with resin carbides are widely used. Among these batteries, in redox flow batteries that are easy to scale up and have excellent durability, the above-mentioned porous substrate can be used directly as a porous carbon electrode.

[0004] Redox flow batteries usually have an external tank for storing electrolyte and an electrolytic cell. Electrolyte containing active materials is pumped from the external tank to the electrolytic cell, while electrochemical energy conversion, i.e., charging and discharging, is performed on electrodes installed in the electrolytic cell. For redox flow batteries, in order to obtain excellent battery characteristics, it is important that the porous carbon electrode installed in the electrolytic cell has excellent hydrophilicity and high reaction activity.

[0005] As a porous carbon electrode with improved hydrophilicity, Patent Document 1 discloses a porous carbon electrode in which conductive carbon particles are bonded to carbon fibers via an ion conductive adhesive. Patent Document 2 discloses a porous carbon electrode using carbon fibers surface-treated with an alkaline degreasing solution. Patent Document 3 discloses a porous carbon electrode using carbon fibers to which a metal oxide is attached.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2017-27920

[0009] Patent Document 2: Japanese Patent Application Publication No. 2007-186823

[0010] Patent Document 3: Japanese Patent Application No. 2005-507980 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, the battery characteristics of conventional redox flow batteries using porous carbon electrodes such as those disclosed in Patent Documents 1 to 3 are still insufficient, and a higher performance porous carbon electrode is desired.

[0013] An object of the present invention is to provide a hydrophilic porous carbon electrode having excellent hydrophilicity, high reaction activity when used in a battery, and excellent battery characteristics, and a method for producing the same.

[0014] Methods for solving problems

[0015] The present invention has the following configurations.

[0016] [1] A hydrophilic porous carbon electrode, which is a sheet-shaped porous carbon electrode formed by bonding carbon fibers via a resin carbide, wherein the water contact angle θ on both sides of the surface in the thickness direction is A The water contact angle θ in the middle of the thickness direction is 0 to 15°. B 0~15°.

[0017] [2] The hydrophilic porous carbon electrode according to [1], wherein the contact angle θ of water on both sides of the electrode in the thickness direction is A The water contact angle θ in the middle of the thickness direction is 0 to 10°. B 0~15°.

[0018] [3] The hydrophilic porous carbon electrode according to [1] or [2], wherein the contact angle θ of water on both sides of the electrode in the thickness direction is A The contact angle θ with water in the middle of the thickness direction B The difference is 0~10°.

[0019] [4] The hydrophilic porous carbon electrode according to any one of [1] to [3], wherein the weight per unit area is 30 to 300 g / m 2 , and the thickness is 0.10~0.80mm.

[0020] [5] The hydrophilic porous carbon electrode according to [4], having a specific surface area of ​​1.0 to 1000 m 2 / g.

[0021] [6] The hydrophilic porous carbon electrode according to [5], wherein non-through holes having an opening size of 0.1 to 5.0 μm and a depth of 0.01 to 1.0 μm are formed on the surface of the carbon fiber.

[0022] [7] The hydrophilic porous carbon electrode according to [5] or [6], wherein Ag is present on the surface of the porous carbon electrode and the through-hole resistance is 3.0 to 6.0 mΩ·cm 2 .

[0023] [8] The hydrophilic porous carbon electrode according to [5], wherein either or both of Ti oxide and Sn oxide exist on the surface of the porous carbon electrode.

[0024] [9] A method for producing a hydrophilic porous carbon electrode, which is the method for producing a hydrophilic porous carbon electrode according to any one of [1] to [8], comprising the following steps (1) to (5).

[0025] Step (1): a step of forming carbon fibers and binder fibers into sheets to obtain a carbon fiber sheet.

[0026] Step (2): a step of impregnating the carbon fiber sheet with a thermosetting resin to obtain a resin-impregnated carbon fiber sheet.

[0027] Step (3): a step of subjecting the resin-impregnated carbon fiber sheet to a heat-pressing treatment to obtain a resin-cured carbon fiber sheet.

[0028] Step (4): a step of carbonizing the resin-cured carbon fiber sheet in an inert atmosphere at 400 to 3000° C. to obtain a porous carbon electrode.

[0029] Step (5): The porous carbon electrode is transported and subjected to heat treatment by flowing an oxidizing gas at 400 to 800° C. in a direction perpendicular to the transport direction of the porous carbon electrode, thereby performing hydrophilization.

[0030]

[10] The method for producing a hydrophilic porous carbon electrode according to [9], wherein the porous carbon electrode is heat treated with the oxidizing gas for 0.5 to 60 minutes.

[0031]

[11] According to the method for producing a hydrophilic porous carbon electrode described in [9] or

[10] , in the above step (5), the above porous carbon electrode is further immersed in a nitric acid solution for electrolysis treatment, washed with water and dried.

[0032]

[12] According to the method for producing a hydrophilic porous carbon electrode according to any one of [9] to

[11] , in the above step (5), both side surfaces of the above porous carbon electrode are further subjected to atmospheric pressure plasma treatment.

[0033]

[13] According to the method for producing a hydrophilic porous carbon electrode described in any one of [9] to

[12] , in the above step (4), the porous carbon electrode is further impregnated with a dispersion of a metal oxide to cause the porous carbon electrode to carry the metal oxide.

[0034] Another aspect of the present invention has the following configuration.

[0035] [A1] A hydrophilic porous carbon electrode, which is a sheet-shaped porous carbon electrode formed by bonding carbon fibers by resin carbide, wherein the water contact angles on both side surfaces in the thickness direction are 0 to 60°, and the water contact angle in the middle portion in the thickness direction is 0 to 60°.

[0036] [A2] The hydrophilic porous carbon electrode according to [A1], wherein the water contact angles on both side surfaces in the thickness direction are 0 to 40°, and the water contact angle in the middle portion in the thickness direction is 0 to 60°.

[0037] [A3] The hydrophilic porous carbon electrode according to [A1] or [A2], wherein the difference between the contact angle of water on both side surfaces in the thickness direction and the contact angle of water in the middle portion in the thickness direction is 0 to 20°.

[0038] [A4] The hydrophilic porous carbon electrode according to any one of [A1] to [A3], wherein the weight per unit area is 50 to 200 g / m 2 , and the thickness is 0.150~0.600mm.

[0039] [A5] A method for producing a hydrophilic porous carbon electrode, which is the method for producing a hydrophilic porous carbon electrode described in any one of [A1] to [A4], comprising the following steps (A1) to (A5).

[0040] Step (A1): a step of forming carbon fibers and binder fibers into sheets to obtain a carbon fiber sheet.

[0041] Step (A2): a step of impregnating the carbon fiber sheet with a thermosetting resin to obtain a resin-impregnated carbon fiber sheet.

[0042] Step (A3): a step of subjecting the resin-impregnated carbon fiber sheet to a heat-pressing treatment to obtain a resin-cured carbon fiber sheet.

[0043] Step (A4): a step of carbonizing the resin-cured carbon fiber sheet in an inert atmosphere at 400 to 3000° C. to obtain a porous carbon electrode.

[0044] Step (A5): a step of subjecting the porous carbon electrode to a hydrophilic treatment to obtain a hydrophilic porous carbon electrode.

[0045] [A6] According to the method for manufacturing a hydrophilic porous carbon electrode described in [A5], as the above-mentioned hydrophilization treatment, the above-mentioned porous carbon electrode is transported and passed through a furnace with an air atmosphere at 400 to 800°C, and the above-mentioned porous carbon electrode is heat-treated for 0.5 to 60 minutes while the gas in the furnace flows in a direction perpendicular to the transport direction of the above-mentioned porous carbon electrode.

[0046] [A7] According to the method for producing a hydrophilic porous carbon electrode described in [A5] or [A6], as the above-mentioned hydrophilization treatment, the above-mentioned porous carbon electrode is immersed in a nitric acid solution for electrolysis treatment, washed with water and dried.

[0047] [A8] According to the method for manufacturing a hydrophilic porous carbon electrode described in [A6] or [A7], as the above-mentioned hydrophilization treatment, either or both of the above-mentioned heat treatment and the above-mentioned electrolysis treatment are performed, and atmospheric pressure plasma treatment is performed on the two side surfaces of the above-mentioned porous carbon electrode.

[0048] Another aspect of the present invention has the following configuration.

[0049] [B1] A porous carbon electrode, which is a sheet-shaped porous carbon electrode formed by bonding carbon fibers via a resin carbide, having a thickness of 0.1 to 0.8 mm and a weight per unit area of ​​30 to 300 g / m 2 , and the specific surface area is 1.0~1000m 2 / g.

[0050] [B2] The porous carbon electrode according to [B1], wherein non-through holes having an opening size of 0.1 to 5.0 μm and a depth of 0.01 to 1.0 μm are formed on the surface of the carbon fiber.

[0051] [B3] The porous carbon electrode according to [B1] or [B2], wherein Ag is present on the surface of the porous carbon electrode and the through resistance is 3.0 to 6.0 mΩ·cm 2 .

[0052] [B4] The porous carbon electrode according to [B1], wherein either or both of Ti oxide and Sn oxide exist on the surface of the porous carbon electrode.

[0053] [B5] The porous carbon electrode according to [B3] or [B4], wherein the water contact angles on both side surfaces in the thickness direction and in the middle portion in the thickness direction are both 0 to 60°.

[0054] [B6] A method for producing a porous carbon electrode, which is the method for producing a porous carbon electrode according to any one of [B1] to [B5], comprising the following steps (B1) to (B6).

[0055] Step (B1): a step of forming carbon fibers and binder fibers into sheets to obtain a carbon fiber sheet.

[0056] Step (B2): a step of impregnating the carbon fiber sheet with a thermosetting resin to obtain a resin-impregnated carbon fiber sheet.

[0057] Step (B3): a step of subjecting the resin-impregnated carbon fiber sheet to a heat-pressing treatment to obtain a resin-cured carbon fiber sheet.

[0058] Step (B4): a step of carbonizing the resin-cured carbon fiber sheet in an inert atmosphere at 400 to 3000° C. to obtain a porous carbon sheet.

[0059] Step (B5): a step of impregnating the porous carbon sheet with a dispersion of a metal oxide to obtain a metal oxide-supporting porous carbon sheet.

[0060] Process (B6): The metal oxide-loaded porous carbon sheet is transported through a furnace with an air atmosphere at 400 to 800°C, and while the gas in the furnace flows in a direction perpendicular to the transport direction of the metal oxide-loaded porous carbon sheet, the metal oxide-loaded porous carbon sheet is heat-treated for 0.5 to 60 minutes to obtain a porous carbon electrode.

[0061] Effects of the Invention

[0062] The hydrophilic porous carbon electrode of the present invention has excellent hydrophilicity and high reaction activity when used in a battery, thereby achieving excellent battery characteristics.

[0063] According to the method for producing a hydrophilic porous carbon electrode of the present invention, it is possible to produce a hydrophilic porous carbon electrode which has excellent hydrophilicity, high reactivity when used in a battery, and can obtain excellent battery characteristics. DETAILED DESCRIPTION

[0064] The hydrophilic porous carbon electrode of the present invention (hereinafter, also referred to as "carbon electrode") is a sheet-shaped porous carbon electrode formed by bonding carbon fibers by resin carbide. In the carbon electrode, a plurality of carbon fibers are dispersed in the sheet in a manner such that the fiber directions of the carbon fibers face random directions, and in this state, the carbon electrode is bonded by resin carbide. That is, the carbon electrode of the present invention is a carbon electrode comprising carbon paper.

[0065] The carbon electrode of the present invention can be suitably used in a redox flow battery.

[0066] As carbon fiber, polyacrylonitrile (PAN) carbon fiber, pitch carbon fiber, rayon carbon fiber can be exemplified. Among them, PAN carbon fiber is preferred. As carbon fiber, one kind can be used alone or two or more kinds can be used in combination.

[0067] The average fiber length of the carbon fiber is preferably 2 to 30 mm, more preferably 2 to 12 mm. That is, the carbon fiber is preferably short carbon fiber. If the average fiber length of the carbon fiber is above the lower limit of the above range, sufficient strength is easily obtained. If the average fiber length of the carbon fiber is below the upper limit of the above range, the dispersibility of the carbon fiber is excellent.

[0068] The average fiber length of carbon fibers is a value obtained by measuring the fiber lengths of 50 randomly selected short fibers while observing the carbon fibers at 50 times or more using a microscope such as a scanning electron microscope, and averaging the values.

[0069] The average fiber diameter of the carbon fiber is preferably 3 to 20 μm, more preferably 3 to 9 μm. When the average fiber diameter of the carbon fiber is at least the lower limit of the above range, the dispersion of the carbon fiber is excellent, so a carbon fiber sheet uniform in the surface direction is obtained. When the average fiber diameter of the carbon fiber is at most the upper limit of the above range, a carbon fiber sheet with high smoothness is obtained.

[0070] In addition, the average fiber diameter of the carbon fiber is a value obtained by magnifying the cross section of the carbon fiber to 50 times or more and observing it using a microscope such as a scanning electron microscope, measuring the fiber diameters of 50 randomly selected single fibers, and averaging their values. In the case of a carbon fiber with a flat cross section, that is, when the cross section has a major diameter and a minor diameter, the major diameter is set as the fiber diameter of the fiber.

[0071] The tensile elastic modulus of the carbon fiber is preferably 200 to 600 GPa, more preferably 200 to 450 GPa.

[0072] The tensile modulus of carbon fiber is obtained by a single fiber tensile test. In the single fiber tensile test, a single fiber is taken out from the carbon fiber, and the elastic modulus of the single fiber is measured using a universal testing machine under the test conditions of a sample length of 5 mm and a tensile speed of 0.5 mm / min. 50 single fibers are selected from the same carbon fiber, their elastic moduli are measured, and the average value is set as the tensile modulus of the carbon fiber.

[0073] The tensile strength of carbon fiber is preferably 3000 to 7000 GPa, more preferably 3500 to 6500 GPa.

[0074] The tensile strength of carbon fiber is obtained by a single fiber tensile test. In the single fiber tensile test, a single fiber is taken out from the carbon fiber, and the strength of the single fiber is measured using a universal testing machine under the test conditions of a sample length of 5 mm and a tensile speed of 0.5 mm / min. 50 single fibers are selected from the same carbon fiber, their strengths are measured, and the average value is set as the tensile strength of the carbon fiber.

[0075] Carbon fibers are obtained by impregnating a bundle of, for example, several thousand to tens of thousands of carbon fiber filaments with a sizing agent, drying and bundling to obtain a carbon fiber bundle, and cutting the carbon fiber bundle continuously or discontinuously into a predetermined length using a roving cutter, a shearing machine, or the like.

[0076] It is preferred that a non-through hole with an opening size of 0.1 to 5.0 μm and a depth of 0.01 to 1.0 μm is formed on the surface of the carbon fiber. As a result, the specific surface area of ​​the carbon electrode is further increased, so the reaction activity when used in a battery is improved, and excellent battery characteristics are further obtained. For example, as described later, such a non-through hole is formed on the surface of the carbon fiber by heat treating a porous carbon electrode loaded with Ag2O.

[0077] The size of the opening of the non-through hole is 0.1 to 5.0 μm, preferably 0.1 to 4.0 μm, and more preferably 0.1 to 3.0 μm. If the size of the opening is greater than the lower limit of the above range, the specific surface area of ​​the carbon electrode is further increased, and the reaction activity when used in a battery is improved. If the size of the opening is less than the upper limit of the above range, a carbon electrode with sufficient strength can be obtained.

[0078] In addition, the size of the opening of the non-through hole refers to the diameter of the circumscribed circle of the opening when the opening is viewed from the front.

[0079] The depth of the non-through hole is 0.01 to 1.0 μm, preferably 0.05 to 1.0 μm, and more preferably 0.1 to 1.0 μm. If the depth of the non-through hole is greater than the lower limit of the above range, the specific surface area of ​​the carbon electrode is further increased, and the reaction activity when used in a battery is improved. If the depth of the non-through hole is less than the upper limit of the above range, a carbon electrode with sufficient strength can be obtained.

[0080] In addition, the depth of the non-through hole refers to the depth of the deepest part of the non-through hole.

[0081] The weight per unit area of ​​the carbon fiber in the carbon electrode is preferably 10 to 140 g / m 2 , more preferably 25 to 100 g / m 2 If the weight per unit area of ​​the carbon fibers is greater than or equal to the lower limit of the above range, a carbon electrode having sufficient strength can be obtained. If the weight per unit area of ​​the carbon fibers is less than or equal to the upper limit of the above range, a carbon electrode in which the carbon fibers are uniformly dispersed can be obtained.

[0082] The content of the carbon fiber in the carbon electrode is preferably 40 to 80% by mass, more preferably 50 to 70% by mass, relative to the total mass of the carbon electrode. If the content of the carbon fiber is above the lower limit of the above range, sufficient strength is easily obtained. If the content of the carbon fiber is below the upper limit of the above range, the content of the resin carbide is relatively increased, so that the carbon fibers are easily and fully bonded to each other.

[0083] Resin carbide is a product obtained by carbonizing resin. The carbon electrode contains a product obtained by carbonizing a binder resin or a binder fiber used in the production of a carbon electrode as resin carbide.

[0084] The binder resin may be any binder resin that has a bonding force with carbon fibers and can be carbonized, and examples thereof include thermosetting resins such as phenolic resins and furan resins. The binder resins may be used alone or in combination of two or more.

[0085] As the phenolic resin, a resol-type phenolic resin obtained by a reaction of phenols and aldehydes in the presence of an alkaline catalyst can be exemplified. A product obtained by dissolving and mixing a solid heat-fusible novolac-type phenolic resin generated by a reaction of phenols and aldehydes in the presence of an acidic catalyst into a resol-type fluid phenolic resin can also be used. In this case, a self-crosslinking type containing, for example, 1,6-hexanediamine as a curing agent is preferably used.

[0086] As the phenol resin, a commercially available product can be used.

[0087] Examples of the phenols include phenol, resorcinol, cresol, and mixed xylenes. As the phenols, one type may be used alone, or two or more types may be used in combination.

[0088] Examples of the aldehydes include formalin, paraformaldehyde, and furfural. As the aldehydes, one type may be used alone, or two or more types may be used in combination.

[0089] As the phenolic resin, a water-dispersible phenolic resin or a water-soluble phenolic resin can be used.

[0090] Examples of the water-dispersible phenolic resin include resol-type phenolic resin emulsions described in JP-A-2004-307815 and JP-A-2006-56960, and water-dispersible phenolic resins referred to as aqueous dispersants.

[0091] Examples of the water-soluble phenolic resin include resol-type phenolic resins having good water solubility as described in JP-A-2009-84382 and the like.

[0092] The content of the resin carbide in the carbon electrode is preferably 20 to 60% by mass, more preferably 25 to 50% by mass, relative to the total mass of the carbon electrode. If the content of the resin carbide is above the lower limit of the above range, it is easy to fully bond the carbon fibers to each other. If the content of the resin carbide is below the upper limit of the above range, the content of the carbon fibers is relatively increased, so it is easy to obtain sufficient strength.

[0093] The carbon electrode may contain other components besides carbon fiber and resin carbide as needed. As other components, carbon powder can be exemplified. By containing carbon powder, the carbon electrode can be expected to improve conductivity.

[0094] Examples of the carbon powder include graphite powder, carbon black, ground fiber, carbon nanotube, carbon nanofiber, coke, activated carbon, and amorphous carbon. The carbon powder may be used alone or in combination of two or more.

[0095] Graphite powder includes a highly crystalline graphite structure, and the average particle size of primary particles thereof is generally several μm to several hundred μm.

[0096] Examples of the graphite powder include pyrolytic graphite, spherical graphite, flaky graphite, massive graphite, amorphous graphite, artificial graphite, and expanded graphite. From the viewpoint of exhibiting electrical conductivity, pyrolytic graphite, spherical graphite, or flaky graphite is preferred.

[0097] Carbon black usually exists in the form of primary particles with an average particle size of tens of μm that fuse together to form a structure (agglomerate) that is further bonded by van der Waals forces. The number of particles per unit mass of carbon black is significantly greater than that of graphite powder. When the concentration is above a certain critical value, the agglomerates are arranged in a three-dimensional network, thus forming a macroscopic conductive path.

[0098] Examples of carbon black include acetylene black, Ketjen black, furnace black, channel black, lamp black, and thermal black.

[0099] The ground fiber may be a fiber obtained by pulverizing the original carbon fiber, or a fiber obtained by pulverizing a recycled product such as a carbon fiber reinforced thermosetting resin molded product, a carbon fiber reinforced thermoplastic resin molded product, or a prepreg. The carbon fiber used as the raw material of the ground fiber may be a PAN-based carbon fiber, a pitch-based carbon fiber, or a rayon-based carbon fiber.

[0100] In the case where the carbon electrode contains carbon powder, the content of the carbon powder in the carbon electrode is preferably 1 to 40% by mass, and more preferably 5 to 30% by mass relative to the total mass of the carbon electrode. If the content of the carbon powder is above the lower limit of the above range, the conductivity is improved, and the surface roughness of the carbon electrode caused by the carbon powder increases the specific surface area of ​​the carbon electrode, thereby improving the reaction activity. If the content of the carbon powder is below the upper limit of the above range, it is difficult to block the diffusion path of the electrolyte.

[0101] In the carbon electrode of the present invention, the contact angle θ of water on both sides of the thickness direction is A The water contact angle θ in the middle of the thickness direction is 0 to 15°. B The contact angle θ of the carbon electrode is 0 to 15°. A and contact angle θ B The range is 0 to 15°, so that the reaction activity when used in a battery is improved, and excellent battery characteristics can be obtained.

[0102] The middle portion of the carbon electrode refers to a portion that is 40 to 60% of the total thickness of the carbon electrode from the surface of the carbon electrode in the thickness direction of the carbon electrode.

[0103] The contact angle θ of the carbon electrode AThe contact angle θ is 0 to 15°, preferably 0 to 13°, more preferably 0 to 10°, and still more preferably 0 to 5°. A If the contact angle θ of the carbon electrode is less than the upper limit, the hydrophilicity is excellent, the reaction activity of the electrode is improved, and excellent battery characteristics can be obtained. A It can be the same or different.

[0104] In addition, the contact angle θ of water in the carbon electrode is A The contact angle is measured using a commercially available contact angle measuring device.

[0105] The contact angle θ of the carbon electrode B The contact angle θ is 0 to 15°, preferably 0 to 13°, more preferably 0 to 10°, and still more preferably 0 to 5°. B When the content is not more than the above upper limit, the electrolyte solution easily permeates into the interior of the electrode, and the reaction activity is improved even inside the electrode, thereby achieving excellent battery characteristics.

[0106] In addition, the contact angle θ of water in the carbon electrode is B The contact angle is measured using a commercially available contact angle measuring device.

[0107] In the present invention, the contact angle θ is preferably A is 0~10°, and the contact angle θ B The angle is 0 to 15°. This further improves the reaction activity of the electrode and enables more excellent battery characteristics to be obtained.

[0108] Contact angle θ in carbon electrode A With contact angle θ B The difference between the contact angle θ and the contact angle θ is preferably 0 to 10°, more preferably 0 to 5°, and still more preferably 0 to 2°. A With contact angle θ B When the difference is equal to or less than the above upper limit, the reaction activity is improved over the entire thickness direction of the electrode, and further excellent battery characteristics are obtained.

[0109] In the present invention, the contact angle θ of the two side surfaces of the carbon electrode in the thickness direction is A With contact angle θ B It is particularly preferred that the difference be within the above range.

[0110] The thickness of the carbon electrode of the present invention is 0.10 to 0.80 mm, and the weight per unit area is preferably 30 to 300 g / m 2 The specific surface area is more preferably 1.0 to 1000 m 2 By controlling the thickness, weight per unit area and specific surface area of ​​the carbon electrode within the above ranges, the reaction activity when used in a battery is further improved, and further excellent battery characteristics are obtained.

[0111] The specific surface area of ​​the carbon electrode is preferably 1.0 to 1000 m 2 / g, more preferably 1.0 to 600 m 2 / g, more preferably 1.0 to 400 m 2 / g, particularly preferably 1.0 to 200 m 2 / g, and most preferably 1.0 to 100 m 2 / g. If the specific surface area is greater than the lower limit of the above range, the reaction activity of the electrode is improved. If the specific surface area is less than the upper limit of the above range, the electrolyte is easily affinity, and the battery characteristics are improved.

[0112] In addition, the specific surface area of ​​the carbon electrode was measured by mercury intrusion porosimetry.

[0113] The weight per unit area of ​​the carbon electrode is preferably 30 to 300 g / m 2 , more preferably 40 to 280, and even more preferably 50 to 200 g / m 2 , particularly preferably 50 to 130 g / m 2 If the weight per unit area of ​​the carbon electrode is greater than the lower limit of the above range, the sheet strength is high and the handleability is excellent, and the electrode can function fully. If the weight per unit area of ​​the carbon electrode is less than the upper limit of the above range, a uniform carbon electrode with less uneven weight per unit area can be obtained, and the productivity is high.

[0114] The thickness of the carbon electrode is preferably 0.10 to 0.80 mm, more preferably 0.10 to 0.70 mm, further preferably 0.15 to 0.60 mm, and particularly preferably 0.19 to 0.60 mm. If the thickness of the carbon electrode is above the lower limit of the above range, a carbon electrode having a sufficient reaction surface area can be obtained. If the thickness of the carbon electrode is below the upper limit of the above range, a carbon electrode with less pressure loss during electrolyte transport can be obtained. In addition, the carbon electrode can be wound into a roll, so the productivity is high.

[0115] In the present invention, it is preferred that Ag exists on the surface of the porous carbon electrode and the through resistance is 3.0 to 6.0 mΩ·cm 2 That is, it is preferred that Ag exists on the surface of the carbon fiber and the resin carbide forming the porous carbon electrode, and the through resistance is controlled within the above range. As a result, the conductivity of the carbon electrode is improved, and the battery characteristics when used in a battery are further improved.

[0116] In the porous carbon electrode, Ag may be uniformly present in the thickness direction, or Ag may be concentrated in the surface layer. For example, as described later, Ag may be precipitated on the surface of the carbon fiber and the resin carbide of the porous carbon electrode by impregnating a dispersion liquid in which Ag2O is dispersed into the porous carbon sheet and heat treating the porous carbon sheet.

[0117] The through resistance of the carbon electrode with Ag on the surface is preferably 3.0 to 6.0 mΩ·cm 2 , more preferably 3.0 to 5.8 mΩ·cm 2 , more preferably 3.0 to 5.6 mΩ·cm 2 If the through resistance is greater than or equal to the lower limit of the above range, the carbon electrode has a sufficient reaction area. If the through resistance is less than or equal to the upper limit of the above range, the conductivity of the carbon electrode is improved, and the battery characteristics when used in a battery are further improved.

[0118] The through-hole resistance of a carbon electrode is the resistance value per unit area in the thickness direction of the electrode and is measured by the following method. 2 A circular sample piece of 1000 nm was sandwiched between a pair of conductive plates, and a voltage when a current of 10 mA was passed was measured while applying a pressure of 1020 N from the top and bottom of the conductive plates to calculate the resistance value per unit area of ​​the carbon electrode. The resistance value can be measured using a resistance meter.

[0119] The amount of Ag loaded in the carbon electrode can be adjusted so that the through resistance is within the above range, preferably 0.1 to 10 parts by mass, more preferably 0.1 to 5.0 parts by mass, relative to 100 parts by mass of the total mass of the carbon fiber and the resin carbide. If the amount of Ag loaded is above the lower limit of the above range, the conductivity of the carbon electrode is improved, and the battery characteristics when used in the battery are further improved. If the amount of Ag loaded is below the upper limit of the above range, it is difficult to block the diffusion path of the electrolyte.

[0120] In the present invention, either or both of Ti oxide and Sn oxide may be present on the surface of the porous carbon electrode. That is, either or both of Ti oxide and Sn oxide may be present on the surface of the carbon fiber and the resin carbide forming the porous carbon electrode. The presence of Ti oxide and Sn oxide improves the hydrophilicity of the electrode, further improves the reaction activity of the electrode, and thus further improves the battery characteristics when used in a battery.

[0121] In the porous carbon electrode, either or both of the Ti oxide and the Su oxide may be present uniformly in the thickness direction or may be concentrated in the surface layer.

[0122] For example, as described later, by impregnating a porous carbon electrode with a dispersion containing Ti oxide and Sn oxide and performing a heat treatment, Ti oxide and Sn oxide can be present on the surfaces of carbon fibers and resin carbide of the porous carbon electrode.

[0123] As Ti oxide, TiO2 can be mentioned.

[0124] Examples of Sn oxides include SnO and SnO 2 , and SnO 2 is preferred.

[0125] The amount of Ti oxide and Sn oxide loaded in the carbon electrode is preferably 0.1 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the total mass of the carbon fiber and the resin carbide. If the amount of Ti oxide and Sn oxide loaded is above the lower limit of the above range, the hydrophilicity of the carbon electrode is improved, and the battery characteristics when used in the battery are further improved. If the amount of Ti oxide and Sn oxide loaded is below the upper limit of the above range, it is difficult to block the diffusion path of the electrolyte.

[0126] (Manufacturing method)

[0127] As a method for producing the carbon electrode of the present invention, there can be mentioned a method having the following steps (1) to (5).

[0128] Step (1): a step of forming carbon fibers and binder fibers into sheets to obtain a carbon fiber sheet.

[0129] Step (2): a step of impregnating the carbon fiber sheet with a thermosetting resin to obtain a resin-impregnated carbon fiber sheet.

[0130] Step (3): a step of subjecting the resin-impregnated carbon fiber sheet to a heat-pressing treatment to obtain a resin-cured carbon fiber sheet.

[0131] Step (4): a step of carbonizing the resin-cured carbon fiber sheet in an inert atmosphere at 400 to 3000° C. to obtain a porous carbon electrode.

[0132] Step (5): The porous carbon electrode is transported and an oxidizing gas at 400 to 800° C. is flowed in a direction perpendicular to the transport direction of the porous carbon electrode to perform a hydrophilic treatment.

[0133] In step (1), carbon fibers and binder fibers are used to form a carbon fiber sheet. The use of the binder fibers together makes it possible to easily form the carbon fibers into sheets.

[0134] As the binder fiber, polyvinyl alcohol (PVA) fiber, polyvinyl acetate fiber, polyethylene fiber, polyethylene terephthalate (PET) fiber, polyethylene (PE) pulp can be exemplified. Among them, PVA fiber and polyethylene fiber are preferred, and PVA fiber and PE pulp are more preferred, from the perspective of excellent bonding strength and being able to more effectively suppress the shedding of carbon fibers. As the binder fiber, one type may be used alone, or two or more types may be used in combination.

[0135] The amount of the binder fiber used is preferably 5 to 100 parts by mass, preferably 10 to 100 parts by mass, more preferably 40 to 100 parts by mass, and particularly preferably 15 to 60 parts by mass relative to 100 parts by mass of the total mass of the carbon fiber. If the amount of the binder fiber used is above the lower limit of the above range, the shedding of the carbon fiber can be more effectively suppressed. If the amount of the binder fiber used is below the upper limit of the above range, a carbon fiber sheet with sufficient strength can be obtained. In addition, a carbon electrode with high liquid permeability can be obtained.

[0136] As a method for making carbon fiber and binder fiber into sheets, there are papermaking methods such as a wet method in which carbon fiber and binder fiber are dispersed in a liquid medium and papermaking is performed, and a dry method in which carbon fiber and binder fiber are dispersed in air and deposited. In view of sheet strength and uniformity of fiber dispersion, the wet method is preferred.

[0137] The liquid medium may be any medium in which the carbon fibers and the binder fibers do not dissolve, and examples thereof include water, and organic solvents such as methanol, ethanol, ethylene glycol, and propylene glycol. From the viewpoint of productivity, water is preferred.

[0138] The carbon fiber sheet may be produced by a continuous method or a batch method, but the continuous method is preferred from the viewpoint of productivity and mechanical strength of the carbon fiber sheet.

[0139] The weight per unit area of ​​the carbon fiber sheet is preferably 10 to 200 g / m 2 .

[0140] The thickness of the carbon fiber sheet is preferably 100 to 2000 μm.

[0141] The carbon fiber sheet is preferably subjected to an interlacing treatment to obtain a carbon fiber sheet having an interlaced structure.

[0142] As the interlacing treatment, mechanical interlacing methods such as needle punching, high-pressure liquid jet methods such as water spunlace, and high-pressure gas jet methods such as steam spunlace can be exemplified. From the perspective of being able to easily suppress the breakage of the carbon fibers caused by the interlacing treatment and easily obtain appropriate interlacing properties, the high-pressure liquid jet method is preferred.

[0143] In the high-pressure liquid jet method, for example, a carbon fiber sheet is placed on a substantially smooth support member, and a columnar flow of liquid, a fan-shaped flow of liquid, a gap flow of liquid, etc., jetted at a pressure of 1 MPa or more is allowed to act to interweave the fibers in the carbon fiber sheet. As a substantially smooth support member, a support member can be used that does not form a support member pattern on the carbon fiber sheet after the interweaving treatment and that the jetted liquid is quickly removed. As a specific example, a metal mesh or plastic mesh or roller with a mesh size of 30 to 200 can be exemplified.

[0144] From the viewpoint of productivity, it is preferred that after the carbon fiber sheet is produced on the support member having a substantially smooth surface, an interlacing treatment by a high-pressure liquid jet method or the like is continuously performed.

[0145] The liquid used in the high-pressure liquid jet method may be any liquid that does not dissolve the fibers to be treated, and is preferably water or deionized water. The water may be warm water.

[0146] The nozzle hole diameter of the high-pressure liquid jet nozzle is preferably 0.06 to 1.0 mm, more preferably 0.1 to 0.3 mm in the case of a columnar flow.

[0147] The distance between the spray hole of the nozzle and the carbon fiber sheet during the treatment is preferably 0.5 to 5 cm.

[0148] From the viewpoint of entanglement of fibers, the pressure of the liquid is preferably 1 MPa or more, more preferably 1.5 MPa or more.

[0149] The interweaving process can be repeated multiple times. For example, after the carbon fiber sheets are interweaved, further carbon fiber sheets can be stacked to interweave, or after the carbon fiber sheets are interweaved from one side, the carbon fiber sheets can be turned over and interweaved again from the opposite side.

[0150] After the interlacing treatment by the high-pressure liquid jet method, the carbon fiber sheet may be dried. The drying method is not particularly limited, and examples thereof include heat treatment using a high-temperature atmosphere furnace, a far-infrared heating furnace, and heat treatment using a hot plate or a hot roll.

[0151] The drying temperature can be set to 20 to 200°C, for example.

[0152] The drying time can be set to, for example, 1 minute to 24 hours.

[0153] In step (2), for example, a thermosetting resin or a resin composition containing a thermosetting resin and other components such as carbon powder is impregnated into the carbon fiber sheet to obtain a resin-impregnated carbon fiber sheet.

[0154] The impregnation method is not particularly limited, and examples thereof include a method of applying a dispersion containing a thermosetting resin or a resin composition to the surface of a carbon fiber sheet, and a method of supplying the dispersion to the carbon fiber sheet by a dip-nip method using an extruder. A method of overlapping a resin film containing a thermosetting resin or a resin composition with a carbon fiber sheet, and then heating and pressurizing the carbon fiber sheet for transfer can also be used.

[0155] As the dispersion medium, water, alcohol, dimethylformamide, and dimethylacetamide are preferred from the viewpoint of handleability and production cost. When water is used as the dispersion medium, a dispersant such as a surfactant may be used to disperse the resin and the carbon powder.

[0156] The amount of the thermosetting resin impregnated into the carbon fiber sheet is preferably 50 to 200 parts by mass, more preferably 80 to 150 parts by mass, based on 100 parts by mass of the carbon fiber sheet.

[0157] The impregnation treatment may be repeated multiple times. For example, after the carbon fiber sheet is impregnated, the carbon fiber sheets may be further stacked and impregnated; or after the carbon fiber sheet is impregnated from one side, the carbon fiber sheet may be turned over and impregnated again from the opposite side.

[0158] The resin-impregnated carbon fiber sheet may be dried after the impregnation treatment. The drying method is not particularly limited, and examples thereof include heat treatment using a high-temperature atmosphere furnace or a far-infrared heating furnace, and heat treatment using a hot plate or a hot roll.

[0159] The drying temperature can be set to, for example, 40 to 120°C.

[0160] The drying time can be set to, for example, 0.1 minute to 24 hours.

[0161] In step (3), the resin-impregnated carbon fiber sheet is subjected to a hot press treatment to cure the thermosetting resin in the resin-impregnated carbon fiber sheet, thereby obtaining a resin-cured carbon fiber sheet.

[0162] As a method for hot pressing the resin-impregnated carbon fiber sheet, there can be exemplified a method of hot pressing the upper and lower surfaces of the resin-impregnated carbon fiber sheet using smooth steel plates; and a method of hot pressing using a continuous belt press. In the case of a continuous method, the hot pressing of the resin-impregnated carbon fiber sheet is preferably performed using a continuous belt press.

[0163] As the pressing method in the continuous belt pressing device, there can be exemplified a method of applying pressure to the belt by linear pressure by roller pressing and a method of pressing by surface pressure by hydraulic head pressing. From the perspective of obtaining a smoother carbon electrode, the method of pressing by surface pressure by hydraulic head pressing is preferred.

[0164] It is preferred that a release agent be applied to the steel plate or belt in advance or release paper be sandwiched between the resin-impregnated carbon fiber sheet and the steel plate or belt during heat pressing to prevent the thermosetting resin or the like from adhering.

[0165] The heating temperature during heat pressing depends on the curing temperature of the thermosetting resin, and is preferably 100 to 400° C., more preferably 150 to 380° C., and further preferably 180 to 360° C. If the heating temperature is at least the lower limit of the above range, the curing of the thermosetting resin is easy to proceed. If the heating temperature is at most the upper limit of the above range, the burning of the thermosetting resin and the binder fiber is easy to be suppressed.

[0166] The pressure applied during heating and pressing is preferably 1 to 20 MPa, more preferably 5 to 15 MPa. If the pressure is above the lower limit of the above range, a carbon electrode with a smooth surface is easily obtained. If the pressure is below the upper limit of the above range, the carbon fibers are less likely to be damaged.

[0167] The time of heat pressing is preferably 0.1 to 5.0 minutes, more preferably 0.1 to 2.0 minutes.

[0168] In step (4), the resin-cured carbon fiber sheet is carbonized to obtain a porous carbon electrode.

[0169] In order to improve the conductivity of the carbon electrode, the carbonization of the resin-cured carbon fiber sheet is performed in an inert atmosphere, preferably using an inert gas such as nitrogen or argon.

[0170] The heating temperature during the carbonization treatment is 400 to 3000° C., preferably 600 to 2500° C., and more preferably 1000 to 2300° C. If the heating temperature during the carbonization treatment is at least the lower limit of the above range, a carbon electrode having excellent electrical conductivity can be easily obtained. If the heating temperature during the carbonization treatment is at most the upper limit of the above range, a carbon electrode having excellent reactivity can be obtained.

[0171] The time for the carbonization treatment can be set to 1 minute to 1 hour.

[0172] In step (4), it is preferred that the porous carbon electrode is further impregnated with a dispersion of a metal oxide to support the metal oxide. This forms the above-mentioned non-through pores on the carbon electrode, thereby increasing the specific surface area.

[0173] Examples of the metal oxide include Ag2O, Ti oxide (TiO2), and Sn oxide (SnO, SnO2). The metal oxide may be used alone or in combination of two or more.

[0174] As the dispersion medium for dispersing the metal oxide, water and alcohol can be exemplified. The water may be deionized water. When water is used as the dispersion medium, a dispersant such as a surfactant can be used.

[0175] The content of the metal oxide in the dispersion is preferably 0.5 to 20% by mass, more preferably 0.5 to 10% by mass, based on the total mass of the dispersion.

[0176] The amount of the metal oxide supported in the porous carbon electrode supporting the metal oxide is preferably 0.1 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, based on 100 parts by mass of the total mass of the carbon fibers and the resin carbide.

[0177] The impregnation treatment with the dispersion of the metal oxide may be repeated multiple times. For example, after the porous carbon electrode is impregnated, further layers of porous carbon electrodes may be impregnated; or after the porous carbon electrode is impregnated from one side, the porous carbon electrode may be turned over and impregnated again from the opposite side.

[0178] After the impregnation treatment, the porous carbon electrode carrying the metal oxide may be dried. The drying method is not particularly limited, and examples thereof include heat treatment using a high-temperature atmosphere furnace, a far-infrared heating furnace, and heat treatment using a hot plate, a hot roll, and the like.

[0179] The drying temperature of the porous carbon electrode supporting the metal oxide can be set to 90 to 300° C., for example.

[0180] The drying time of the porous carbon electrode supporting the metal oxide can be set to, for example, 0.5 minutes to 2 hours.

[0181] In step (5), the porous carbon electrode is transported and an oxidizing gas at 400 to 800° C. is caused to flow in a direction perpendicular to the transport direction of the porous carbon electrode to perform heat treatment. Thus, a carbon electrode is hydrophilized and satisfies the above-mentioned water contact angle conditions. For example, a method can be exemplified in which a porous carbon electrode is transported and passed through a furnace with an air atmosphere at 400 to 800° C., and an oxidizing gas is caused to flow in a direction perpendicular to the transport direction of the porous carbon electrode in the furnace while the porous carbon electrode is heat treated.

[0182] As the oxidizing gas, oxygen, air, and carbon dioxide can be exemplified. Among them, air is preferred in view of the use cost. As the oxidizing gas, one kind may be used alone, or two or more kinds may be used in combination.

[0183] The temperature in the furnace is 400 to 800° C., preferably 500 to 750° C., and more preferably 550 to 700° C. If the temperature in the furnace is above the lower limit of the above range, the hydrophilicity is excellent, and it is easy to obtain a carbon electrode with high reaction activity in the battery. If the temperature in the furnace is below the upper limit of the above range, a carbon electrode with sufficient strength can be obtained.

[0184] The heat treatment time is preferably 5 to 60 minutes, more preferably 0.5 to 10 minutes, and further preferably 0.5 to 5 minutes. If the heat treatment time is above the lower limit of the above range, it is easy to obtain a carbon electrode with excellent hydrophilicity. If the heat treatment time is below the upper limit of the above range, the productivity is high.

[0185] When Ag2O is used as the metal oxide in step (4), a reduction reaction represented by 2Ag2O→4Ag+O2 occurs during the heat treatment, and Ag is precipitated on the surfaces of the carbon fibers and the resin carbide, thereby obtaining a carbon electrode with excellent electrical conductivity.

[0186] In addition, Ag2O acts as an oxidant to introduce functional groups such as carboxyl and hydroxyl groups into the carbon fiber. In addition, non-through holes are formed on the surface of the carbon fiber, and the specific surface area of ​​the porous carbon electrode is further increased. Thus, the above functional groups are introduced into the carbon electrode at a high density, so the reaction activity of the electrode is further improved. It is speculated that the formation of the non-through holes on the surface of the carbon fiber is caused by the above reduction reaction.

[0187] When Ti oxide (TiO2) or Sn oxide (SnO, SnO2) is used as the metal oxide in step (4), these metal oxides exist on the surface of the carbon fibers and resin carbides in the obtained carbon electrode, and a carbon electrode with better hydrophilicity can be obtained.

[0188] As a hydrophilic treatment, in addition to the heat treatment using an oxidizing gas, a method of further immersing the porous carbon electrode in a nitric acid solution for electrolytic treatment, washing with water and drying can be adopted. In this case, the electrolytic treatment can be performed after the heat treatment using an oxidizing gas, or the heat treatment using an oxidizing gas can be performed after the electrolytic treatment.

[0189] Examples of the nitric acid solution include aqueous solutions having a nitric acid concentration of 0.1 to 13.0 mol / L, and the nitric acid concentration is preferably 0.5 to 5 mol / L.

[0190] The temperature of the nitric acid solution during the electrolytic treatment is preferably 5 to 40° C., more preferably 10 to 30° C. When the temperature is at least the lower limit of the above range, a carbon electrode having excellent hydrophilicity can be easily obtained. When the temperature is at most the upper limit of the above range, productivity is high.

[0191] The treatment time of the electrolytic treatment is preferably 0.1 to 5.0 minutes, more preferably 0.5 to 3.0 minutes. If the treatment time is above the lower limit of the above range, it is easy to obtain a carbon electrode with excellent hydrophilicity. If the treatment time is below the upper limit of the above range, the productivity is high.

[0192] As a hydrophilic treatment, in addition to the heat treatment using an oxidizing gas, or the heat treatment and electrolysis treatment using an oxidizing gas, an atmospheric pressure plasma treatment can be further performed on both sides of the porous carbon electrode. The order of the atmospheric pressure plasma treatment is not particularly limited, and it can be before the heat treatment and electrolysis treatment, after the heat treatment and electrolysis treatment, or between the heat treatment and electrolysis treatment.

[0193] Atmospheric pressure plasma treatment can be performed directly or remotely. The so-called direct method is a method in which a porous carbon electrode is arranged between two parallel plate electrodes for treatment. The so-called remote method is a method in which the plasma generated between the electrodes is sprayed onto the porous carbon electrode for treatment.

[0194] The introduced gas introduced into the plasma processing chamber during plasma processing can be any gas that stably generates plasma gas, and is preferably a gas that contains an inert gas in a range of 97.0 volume % to 99.99 volume % and an active gas in a range of 0.01 volume % to 3.0 volume %.

[0195] Examples of the inert gas include nitrogen gas and argon gas.

[0196] Examples of the active gas include oxygen, hydrogen, and carbon monoxide.

[0197] As described above, in the carbon electrode of the present invention, the contact angle θ of water on both sides of the surface in the thickness direction is A The contact angle θ with water in the middle of the thickness direction B are all controlled within a specific range. Thus, the contact angle of water is low not only on the surface of the carbon electrode but also in the middle part in the thickness direction, and the hydrophilicity is excellent, so the reaction activity of the electrode is high throughout the entire thickness direction. Therefore, by using the carbon electrode of the present invention in a redox flow battery, excellent battery characteristics can be obtained.

[0198] Furthermore, in the carbon electrode of the present invention, by controlling the thickness, weight per unit area and specific surface area within specific ranges, the reaction activity of the electrode is further improved.

[0199] Hereinafter, the present invention will be specifically described by way of Examples, but the present invention is not limited to the following description.

[0200] [Measurement of water contact angle]

[0201] The contact angle θ of water on both sides of the carbon electrode in the thickness direction A The contact angle of water was measured at 10 locations, 5 on the front and 5 on the back, for each sample using a contact angle meter (manufactured by Matsubo Co., Ltd.), and the average value was defined as the contact angle θ. A The measurement positions were set to five positions that were uniform with respect to the sheet width direction. The contact angle θ of water at the middle portion in the thickness direction of the carbon electrode B Double-sided tape was pasted on both surfaces of the carbon electrode and peeled off to expose the surface in the middle of the thickness direction. The contact angle of water was measured at 10 locations for each sample, and the average value was set as the contact angle θ. BThe position in the thickness direction of the surface of the middle portion to be measured was set to be a portion located at a position of 0.4 to 0.6 relative to the thickness 1 of the carbon electrode.

[0202] [Evaluation of battery characteristics]

[0203] The battery characteristics of the redox flow battery using the carbon electrode of each example were measured as follows.

[0204] The carbon electrode was cut into an electrode area of ​​9 cm with a length of 3 cm in the vertical direction (liquid flow direction) and a width of 3 cm. 2 , assembled into a single cell. When using a thin carbon electrode, the number of blocks was adjusted so that the thickness of the carbon electrode became 0.60 mm. Nafion 212 membrane was used as the ion exchange membrane. At 70 mA / cm 2 The charge was carried out until 1.45V, and the discharge characteristics were confirmed using an electrochemical measuring device manufactured by Solartron. The results are shown in Tables 1 and 2 as the maximum output density. In addition, the positive electrode electrolyte used a 3.0 mol / L sulfuric acid aqueous solution of 1.0 mol / L vanadium sulfate, and the negative electrode electrolyte used a 3.0 mol / L sulfuric acid aqueous solution of 1.0 mol / L vanadium sulfate. The amount of electrolyte is greatly excessive relative to the single cell and piping. The liquid flow rate is set to 20 mL per minute and measured at 30 ° C.

[0205] [Specific surface area]

[0206] The specific surface area of ​​the carbon electrode was measured by mercury intrusion porosimetry using a mercury porosimeter.

[0207] [Measurement of through resistance]

[0208] The through-hole resistance of the carbon electrode was measured by the following method.

[0209] The 10.2 cm 2 The circular sample piece was clamped by a pair of conductive plates, and the voltage when a current of 10 mA was passed was measured while applying pressure of 1020 N from the top and bottom of the conductive plates, and the resistance per unit area of ​​the carbon electrode was calculated. As a measuring device, a low resistance meter (Agilent 34420A, manufactured by Agilent) was used.

[0210] [Example A1]

[0211] 100 parts by mass of carbon fibers (PAN-based carbon fibers, average fiber diameter: 7 μm, average fiber length: 3 mm) are uniformly dispersed in water to separate into single fibers. After being fully dispersed, 80 parts by mass of polyethylene pulp (manufactured by Mitsui Chemicals, Inc., trade name SWP) as a binder fiber and 20 parts by mass of PVA fibers (manufactured by Kuraray Co., Ltd., "VPB105-1", average fiber length: 3 mm) are uniformly dispersed to prepare a dispersion.

[0212] After the dispersion was made into paper, it was dried to obtain a paper having a weight per unit area of ​​40 g / m 2 Carbon fiber sheet.

[0213] The carbon fiber sheet was impregnated with a methanol solution containing 30 mass % of a phenolic resin (manufactured by DIC Corporation, "phenolite J-325") as a thermosetting resin, and dried at 40°C for 15 minutes using a hot air dryer to obtain a carbon fiber sheet having a weight per unit area of ​​60 g / m 2 Resin impregnated carbon fiber sheet.

[0214] The resin-impregnated carbon fiber sheet was passed through a double belt press apparatus and subjected to heat pressing treatment at 250° C. and 10 MPa for 1 minute to obtain a resin-cured carbon fiber sheet.

[0215] The resin-cured carbon fiber sheet was heated and carbonized at 2000° C. for 15 minutes in a nitrogen atmosphere using a carbonization furnace to obtain a porous carbon electrode having a thickness of 200 μm.

[0216] The porous carbon electrode was conveyed while passing through a furnace with an air atmosphere at 680°C. The air was made to flow in a direction perpendicular to the conveying direction of the porous carbon electrode in the furnace while heat treating the electrode for 3 minutes to obtain a hydrophilic porous carbon electrode.

[0217] The water contact angle θ of both sides of the obtained hydrophilic porous carbon electrode in the thickness direction is A The contact angle of water in the middle of the thickness direction is θ B is 5°.

[0218] [Example A2]

[0219] A porous carbon electrode was obtained in the same manner as in Example A1.

[0220] The porous carbon electrode was transported while passing through a furnace with an air atmosphere at 680°C. The air was made to flow in a direction perpendicular to the transport direction of the porous carbon electrode in the furnace while being heat treated for 3 minutes. The atmospheric pressure plasma treatment was further performed to obtain a hydrophilic porous carbon electrode. In the atmospheric pressure plasma treatment, a mixed gas of nitrogen: oxygen = 99.99:0.0100 (volume %) was used as the introduction gas into the plasma treatment chamber of the atmospheric pressure plasma device AP-T03-S230 (Sekisui Chemical Co., Ltd.) and introduced at 75 L / min. The plasma gas ejection port of the plasma device was arranged at 3 mm from the surface of the porous carbon electrode so that the plasma gas was ejected to the porous carbon electrode from the perpendicular direction of the porous carbon electrode. In this state, the porous carbon electrode was plasma treated for 0.5 seconds at an output power of 375 W. This treatment was performed on both sides of the porous carbon electrode.

[0221] The water contact angle θ of the two sides of the obtained hydrophilic porous carbon electrode in the thickness direction is A The water contact angle θ in the middle of the thickness direction is 2° and 3° respectively. B is 5°.

[0222] [Comparative Example A1]

[0223] A porous carbon electrode was obtained in the same manner as in Example A1.

[0224] The porous carbon electrode was immersed in an aqueous solution (25° C.) having a nitric acid concentration of 3 mol / L for 2 minutes for electrolysis treatment, and then washed with water and dried.

[0225] The water contact angle θ of the two sides of the porous carbon electrode in the thickness direction is obtained. A The water contact angle θ in the middle of the thickness direction is 32° and 34° respectively. B It is 38°.

[0226] [Comparative Example A2]

[0227] A porous carbon electrode was obtained in the same manner as in Example A1.

[0228] The porous carbon electrode was immersed in an aqueous solution (25°C) with a concentration of 3 mol / L of nitric acid for 2 minutes for electrolysis treatment, washed with water and dried, and then further subjected to atmospheric pressure plasma treatment. In the atmospheric pressure plasma treatment, a mixed gas of nitrogen: oxygen = 99.99:0.0100 (volume %) was used as the introduction gas into the plasma treatment chamber of the atmospheric pressure plasma device AP-T03-S230 (Sekisui Chemical Co., Ltd.), and introduced at 75 L / min. The plasma gas ejection port of the plasma device was arranged at 3 mm from the two side surfaces of the porous carbon electrode so that the plasma gas was ejected to the porous carbon electrode from the vertical direction of the porous carbon electrode. In this state, the porous carbon electrode was subjected to plasma treatment for 0.5 seconds at an output power of 375 W. This treatment was performed on both side surfaces of the porous carbon electrode.

[0229] The water contact angle θ of the two sides of the porous carbon electrode in the thickness direction is obtained. A The contact angle of water in the middle of the thickness direction is θ, which is 19° and 18° respectively. B is 25°.

[0230] [Comparative Example A3]

[0231] A porous carbon electrode was obtained in the same manner as in Example 1 except that the hydrophilization treatment was not performed.

[0232] Table 1 shows the evaluation results of the battery characteristics of the redox flow battery using the carbon electrode of each example.

[0233] [Table 1]

[0234]

[0235] As shown in Table 1, the contact angle θ was used. A and contact angle θ B The redox flow batteries of the hydrophilic porous carbon electrodes of Examples A1 and A2, both of which were within the range of 0 to 15°, were excellent in battery characteristics.

[0236] The contact angle θ was used A and contact angle θ B The porous carbon electrodes of Comparative Examples A1 to A3, in which at least one of the values ​​of is outside the range of 0 to 15°, had poor battery characteristics of the redox flow batteries.

[0237] [Example B1]

[0238] 100 parts by mass of carbon fibers (PAN-based carbon fibers, average fiber diameter: 7 μm, average fiber length: 3 mm) are uniformly dispersed in water to separate into single fibers. After being fully dispersed, 80 parts by mass of polyethylene pulp (manufactured by Mitsui Chemicals, Inc., trade name SWP) as a binder fiber and 20 parts by mass of PVA fibers (manufactured by Kuraray Co., Ltd., "VPB105-1", average fiber length: 3 mm) are uniformly dispersed to prepare a dispersion.

[0239] After the dispersion was made into paper, it was dried to obtain a paper having a weight per unit area of ​​40 g / m 2 Carbon fiber sheet.

[0240] The carbon fiber sheet was immersed in a dispersion in which a phenolic resin (DIC Corporation, "phenolite J-325") as a thermosetting resin was dispersed in methanol at a rate of 30 mass %, and the carbon fiber sheet was impregnated with the thermosetting resin and dried at 60° C. for 15 minutes using a hot air dryer to obtain a carbon fiber sheet having a weight per unit area of ​​60 g / m 2 Resin impregnated carbon fiber sheet.

[0241] The resin-impregnated carbon fiber sheet was passed through a double belt press apparatus and subjected to heat pressing treatment at 250° C. and 10 MPa for 1 minute to obtain a resin-cured carbon fiber sheet.

[0242] The resin-cured carbon fiber sheet was heated and carbonized at 2000° C. for 15 minutes in a nitrogen atmosphere using a carbonization furnace to obtain a porous carbon electrode having a thickness of 210 μm.

[0243] The porous carbon electrode was immersed in a dispersion in which Ag2O (manufactured by Nacalai Tesque Co., Ltd.) was dispersed in water at a concentration of 10 mass %, and was impregnated with Ag2O, and dried at 100°C for 1 hour using a hot air dryer.

[0244] The porous carbon electrode loaded with Ag2O was transported through a furnace with an air atmosphere at 400°C, and the air was flowed in a direction perpendicular to the transport direction of the porous carbon electrode in the furnace while heat treating for 10 minutes to obtain a hydrophilic porous carbon electrode. The obtained hydrophilic porous carbon electrode had a thickness of 0.21 mm and a weight per unit area of ​​57 g / m 2 , with a specific surface area of ​​6.6m 2 / g.

[0245] [Example B2]

[0246] A hydrophilic porous carbon electrode was prepared in the same manner as in Example B1 except that the amount of carbon fiber, binder fiber, and thermosetting resin used was adjusted and a porous carbon sheet with a thickness of 630 μm was used. The hydrophilic porous carbon electrode obtained had a thickness of 0.63 mm and a weight per unit area of ​​178 g / m 2 , with a specific surface area of ​​7.2m 2 / g.

[0247] [Comparative Example B1]

[0248] A porous carbon electrode was produced in the same manner as in Example B1 except that TiO2 was used instead of Ag2O. The obtained porous carbon electrode had a thickness of 0.21 mm and a weight per unit area of ​​65 g / m 2 , with a specific surface area of ​​1.2m 2 / g.

[0249] [Comparative Example B2]

[0250] A porous carbon electrode was produced in the same manner as in Example B1 except that SnO2 was used instead of Ag2O. The obtained porous carbon electrode had a thickness of 0.21 mm and a weight per unit area of ​​66 g / m 2 , with a specific surface area of ​​2.4m 2 / g.

[0251] [Comparative Example B3]

[0252] A porous carbon electrode was obtained in the same manner as in Example B1 except that the impregnation treatment with the Ag2O dispersion and the heat treatment were not performed. The obtained porous carbon electrode had a thickness of 0.21 mm and a weight per unit area of ​​62 g / m 2 , with a specific surface area of ​​0.9m 2 / g.

[0253] The thickness, weight per unit area, specific surface area, and contact angle θ of the porous carbon electrode of each example were A , contact angle θ B Table 2 shows the measurement results of the penetration resistance and the evaluation results of the battery characteristics of the redox flow battery using the porous carbon electrode.

[0254] [Table 2]

[0255]

[0256] As shown in Table 2, the contact angle θ A and contact angle θ BThe hydrophilic porous carbon electrodes of Examples B1 and B2, which were all within the range of 0 to 15° and whose thickness, weight per unit area and specific surface area were within specific ranges, showed excellent battery characteristics of redox flow batteries.

[0257] On the other hand, the contact angle θ A and contact angle θ B Comparative Examples B1 and B2, and the contact angle θ A and contact angle θ B In the porous carbon electrode of Comparative Example B3 having a large surface area and a small specific surface area, the battery characteristics of the redox flow battery were poor.

Claims

1. A porous carbon electrode, which is a sheet-shaped porous carbon electrode formed by bonding carbon fibers via a resin carbide. The contact angle of water on both sides of the thickness direction is θ A The water contact angle θ in the middle of the thickness direction is 0 to 15°. B 0~15°, The specific surface area of ​​the porous carbon electrode is 1.0 to 1000 m 2 / g, Through resistance: 3.0~6.0mΩ·cm 2 .

2. The porous carbon electrode according to claim 1, wherein the contact angle θ of water on both sides of the electrode in the thickness direction is A The water contact angle θ in the middle of the thickness direction is 0 to 10°. B 0~15°.

3. The porous carbon electrode according to claim 1 or 2, wherein the contact angle θ of water on both sides of the electrode in the thickness direction is A The contact angle θ with water in the middle of the thickness direction B The difference is 0~10°.

4. The porous carbon electrode according to claim 1 or 2, wherein the weight per unit area is 30 to 300 g / m 2 , and the thickness is 0.10~0.80mm. 5 . The porous carbon electrode according to claim 1 , wherein non-through holes having an opening size of 0.1 to 5.0 μm and a depth of 0.01 to 1.0 μm are formed on the surface of the carbon fiber. The porous carbon electrode according to claim 1 or 2, wherein Ag exists on the surface of the porous carbon electrode. 7 . The porous carbon electrode according to claim 1 , wherein either or both of Ti oxide and Sn oxide exist on the surface of the porous carbon electrode.

8. A method for producing a porous carbon electrode, which is the method for producing a porous carbon electrode according to any one of claims 1 to 7, comprising the following steps (1) to (5): Step (1): a step of forming carbon fiber and binder fiber into sheets to obtain a carbon fiber sheet, Step (2): a step of impregnating the carbon fiber sheet with a thermosetting resin to obtain a resin-impregnated carbon fiber sheet, Step (3): a step of subjecting the resin-impregnated carbon fiber sheet to a heat-pressing treatment to obtain a resin-cured carbon fiber sheet, Step (4): a step of carbonizing the resin-cured carbon fiber sheet in an inert atmosphere at 400 to 3000° C. to obtain a porous carbon electrode. Step (5): The porous carbon electrode is transported and subjected to heat treatment by flowing an oxidizing gas at 400 to 800° C. in a direction perpendicular to the transport direction of the porous carbon electrode, thereby performing hydrophilization. 9 . The method for producing a porous carbon electrode according to claim 8 , wherein the porous carbon electrode is heat-treated with the oxidizing gas for 0.5 to 60 minutes.

10. The method for producing a porous carbon electrode according to claim 8 or 9, wherein in the step (5), the porous carbon electrode is further immersed in a nitric acid solution for electrolytic treatment, washed with water and dried.

11. The method for producing a porous carbon electrode according to claim 8 or 9, wherein in the step (5), both side surfaces of the porous carbon electrode are further subjected to atmospheric pressure plasma treatment.

12. The method for producing a porous carbon electrode according to claim 8 or 9, wherein in the step (4), the porous carbon electrode is further impregnated with a dispersion of a metal oxide to allow the porous carbon electrode to support the metal oxide.

Citation Information

Patent Citations

  • Resol type phenol resin emulsion for papermaking, and its production method

    JP2004307815A

  • Hydrophilic treatment of carbon fiber structures

    JP2005507980A

  • Resol type phenol resin emulsion and method for producing the same

    JP2006056960A

  • Method for treating surface of carbon fiber, hydrophilic carbon fiber and electrode and method for producing the same

    JP2007186823A

  • Manufacturing method of resol type phenolic resin

    JP2009084382A